A Review of In-Vitro Analytical Methodologies for Accurate Moisture Content Measurement in Pericardium Tissue (International Journal of Scientific Research in Science and Technology, 2025)
Bovine pericardium is widely used in medical device applications, particularly in the production of bioprosthetic heart valves, due to its exceptional properties such as high tensile strength, flexibility, and biocompatibility. The moisture content of this tissue plays a crucial role in determining its mechanical properties, stability, and overall performance in medical devices. This article presents an overview of the analytical methods for measuring moisture content in bovine pericardium and highlights their importance in ensuring the quality and safety of medical products. The aim of the study was to assess the moisture content in bovine pericardium using standard analytical techniques, with a focus on the impact of moisture levels on the material’s performance. The objective of this experiment was to determine the moisture content of pericardium tissue samples by calculating the difference in weight before and after drying. This test aims to provide an accurate measure of tissue hydration under controlled conditions. Additional methods reviewed include Near-Infrared Spectroscopy (NIR), Microwave Drying, Karl Fischer Titration, and Thermogravimetric Analysis (TGA). The results of the moisture content testing demonstrated that the average moisture content across various samples of bovine pericardium was approximately 73.47%, with a range between 73.1% and 73.8%. These values are consistent with the optimal moisture content required for maintaining the material’s flexibility and strength. The study concluded that regular monitoring and precise control of moisture content are essential for ensuring the structural integrity and performance of bovine pericardium-based medical devices. Standardized testing and adherence to regulatory standards are critical in maintaining the quality and safety of these products. Future research should explore advanced preservation techniques to enhance the stability and usability of bovine pericardium for biomedical applications.